Egg Quality and Blood Hematology of Magelang Laying Duck Fed with Diets Containing Different Ratios of Omega 3 and Omega 6 Fatty Acids and Organic Zn - Sumiati; Darmawan, A.; Wiryawan, K.G. (International Journal of Poultry Science, 2016)
Objective: The aim of this study was to investigate the effect of feeding diets containing different amounts of omega-3 and omega-6 fatty acids and organic zinc on egg quality and blood hematology. Methodology: Ninety Magelang laying ducks of 21 weeks old were randomly divided into 18 experimental units in a completely randomized design with 6 treatments and 3 replications. The treatment diets included the following: R0 = Diet without palm oil, fish oil or organic zinc with ratio of 1:5 omega-3 and omega-6, R1= Diet with ratio of 1:1.5 omega-3 and omega-6+200 ppm organic zinc, R2 = Diet with ratio of 1:3 omega-3 and omega-6+200 ppm organic zinc, R3 = Diet with ratio of 1:4.5 omega-3:omega-6+200 ppm organic zinc, R4 = Diet with ratio of 1:6 omega-3 and omega-6+200 ppm organic zinc, R5 = Diet with ratio of 1:7.5 omega-3 and omega-6+200 ppm organic zinc. Results: The R2 treatment decreased significantly (p<0.01) yolk cholesterol but the highest value of vitamin A was resulted by R5. The best ratio of omega-3 and omega-6 was produced by R2 (1:3.4). The R1 treatment resulted the lowest heterophil to lymphocyte ratio. Conclusion: Conclusively, feeding diets with ratio of omega-3:omega-6 fatty acids of 1:3+200 ppm organic zinc produced the best ratio of omega-3:omega-6 in yolk as well as increased vitamin A content, decreased yolk cholesterol content and did not interfere ducks physiologically.